Hearing aid combined with virtual reality function - Tannor Ophelia Amanda (Boston, USA, 2020)
In this paper the structure scheme of a smart hearing aid with augmented reality was proposed. This scheme consists of 6 blocks: sensor (microphone), ADC, microprocessor or microcontroller, battery, Bluetooth module, speaker. Such a device should not only improve hearing but also increase the psychological confidence of a person. The next stage of work is the development of an electrical circuit diagram of the device and the assembly of the prototype
Keywords: smart hearing aid; virtual reality; augmented reality; structure scheme